Parallel processes and divergent outcomes: The transformation of the economies of former Socialist countries - Alexander Chepurenko; Miklos Szanyi (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2021)
The paper deals with the problems of diverging developmental trajectories of former Socialist economies of the Central and South-Eastern European countries as well as of the former USSR republics. The purpose is exploring the developmental trends of three groups of economies - ECE, Balkans and some of the CIS - which started from seemingly same initial base, but later showed some specifics both regarding the socio-economic orders and the dynamics of internal developments. The paper argues that over the 30 years of post-Socialist development, these countries moved over certain periods of adaptation and mimicry (mostly importing or imitating institutions of the established market economies and democracies), the later stage of evaluating of the experience and developing of some hybrid socio-economic models, and the contemporary stage of what is called "dependent", or "periphery" capitalisms in ECE and Balkan countries vs. "backslide transition" in Russia and some other CIS countries. Thus, the outcomes of the systemic transition are shown as problematic, fragile and different. The paper refers these divergences to a set of differing preconditions as well as institutional traps which occurred during the systemic change itself, and shows both commonalities as well as specifics of post-Socialist socio-economic development also within each of the three sub-groups of countries. The paper bases on the desk research of the relevant literature and own investigations.
Keywords: P20; P21; P30; P51; 330; transition; post-Socialist economies; Central and Eastern Europe; systemic comparison